Державна інноваційна політика вдосконалення інвестиційно-будівельного комплексу України - Шведун, Вікторія Олександрівна; Грень, Лариса Миколаївна (Чорноморський національний університет ім. Петра Могили, 2020)
У статті запропоновано напрями розвитку державної інноваційної політики вдосконалення інвестиційно-будівельного комплексу України. Зокрема, охарактеризовано основні напрями і технології інноваційної діяльності в будівництві в Україні. Проаналізовано структуру і динаміку зміни капітальних інвестицій у будівельний комплекс України. Виокремлено напрями формування та реалізації державної інноваційної політики щодо вдосконалення інвестиційно-будівельного комплексу України. Серед основних заходів, реалізація яких дозволила б вивести будівельний комплекс України з кризового стану, виділено такі: перехід до реальної структурної й інституційної реформи української економіки; реалізація ефективної інвестиційної політики, орієнтованої на подолання поточних структурних змін негативного впливу; формування державно-приватного партнерства. Запропоновано впровадження гарантій для будівельних компаній в складі державно-приватного-партнерства, які уможливлять отримання більшої фінансової стійкості: гарантії завершення будівництва в розумні терміни за рахунок участі держави; гарантії одержання найменшої на ринку ціни за рахунок відсутності паразитних (трансакційних) витрат і оптимізації витрат на придбання земельних ділянок, будівництво та інфраструктуру.

The article proposes directions of development of the state innovation policy on improving of the investment and construction complex of Ukraine. In particular, the following main directions and technologies of innovation activity in construction in Ukraine are described: innovations in the design of residential buildings, social and industrial facilities, transport systems and communications; new technologies, materials, equipment, construction management methods related to complex safety, energy effi ciency and ecology, which contributes to improving of quality and reducing of construction time. The structure and dynamics of changes in capital investments in the construction complex of Ukraine are analyzed. The directions of formation and implementation of the state innovation policy on improvement of investment and construction complex of Ukraine are highlighted. The following ones are highlighted among the main measures whose implementation would make it possible to remove the construction complex of Ukraine from the crisis state: transition to real structural and institutional reform of the Ukrainian economy; implementation of effective investment policies aimed at overcoming current structural changes of negative impact; formation of publicprivate partnerships. It is proposed to introduce the following guarantees for construction companies as part of a public-private partnership, which will make them more fi nancial sustainable: guarantees of construction completion within a reasonable time at the expense of state participation; guarantees of the lowest price on the market due to absence of parasitic (transaction) costs and optimization of costs for land, construction and infrastructure acquisition. Thus, the state in the investment and construction sector should lay objective prerequisites for effective operation of both individual construction companies and integrated structures in general in market conditions, due to the constant need for construction products, in particular in the social sphere, with the possibility of determining of the optimal proportions of the market economy and state regulation. As foreign experience shows, such state participation makes it possible to turn the construction industry into one of the most profi table sectors of the national economy.
State innovative policy of improving of the investment and construction complex of Ukraine
Keywords: державно-приватне партнерство; інвестиційна політика; капітальні інвестиції; будівництво; state innovation policy; public-private partnership; investment policy; capital investments